Knowing Customers Better: An Experimentation of Twit Marketing in the e-Commerce Industry - Al Turki, Hamad; Fayyoumi, Ayham (International Journal of Advanced Corporate Learning (iJAC), 2014)
Internet gives incredible opportunities for companies to learn about their consumers and provides different channels for marketing. Otlobli.com website (an e-commerce company established in Saudi Arabia), uses different channels, such as: Google AdWords, newspaper website banners, official thread on a famous online forum and, Twitter. A marketing tool has been developed to enhance the effectiveness of marketing on Twitter. This research investigates the impact of the developed system. Website access from these various channels was examined, in addition to the number of visitors who have completed an order. Results showed that the tool caused around 49% increase in the number of visits from Twitter, and comparatively, a good percentage of them completed an order.